2017
DOI: 10.1002/2017gl075141
|View full text |Cite
|
Sign up to set email alerts
|

Crustal and Uppermost Mantle Structure Across the Tibet‐Qinling Transition Zone in NE Tibet: Implications for Material Extrusion Beneath the Tibetan Plateau

Abstract: Based on a dense linear seismic array traversing the eastern margin of the Tibetan Plateau into the Qinling Belt, we conducted a joint inversion of receiver functions and surface wave dispersion curves under P wave velocity constraints and simultaneously derived a crustal and uppermost mantle Vs profile with a Vp/Vs profile. Our observations indicate that the Qinling Belt, of which the lower crust exhibits Vp/Vs values less than 1.8 that are indicative of an intermediate to felsic composition, is currently not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 45 publications
2
23
0
1
Order By: Relevance
“…The lateral variation in crustal thickness in our study region generally agree with previous receiver function studies and deep seismic sounding results, which show that the crust under the NE, eastern, and SE margins of the Tibetan plateau are significantly thicker than that under adjacent regions (e.g., He et al, 2014;Pan & Niu, 2011;Wang et al, 2010;Xu et al, 2014;Zhang et al, 2010). The crustal thickness remains almost unchanged beneath the western Qinling orogenic belt east of 104°E, in agreement with a flat Moho measured recently with a small linear array (Ye et al, 2017). We also note that the crust beneath the Liupan Shan at 36°N is~50-km thick, which is slightly thinner than the estimate of 55-60 km obtained from joint inversion of receiver functions and Rayleigh wave dispersions (Guo & Chen, 2017).…”
Section: Moho Topography and Crustal Poisson's Ratio From Receiver Fusupporting
confidence: 92%
See 1 more Smart Citation
“…The lateral variation in crustal thickness in our study region generally agree with previous receiver function studies and deep seismic sounding results, which show that the crust under the NE, eastern, and SE margins of the Tibetan plateau are significantly thicker than that under adjacent regions (e.g., He et al, 2014;Pan & Niu, 2011;Wang et al, 2010;Xu et al, 2014;Zhang et al, 2010). The crustal thickness remains almost unchanged beneath the western Qinling orogenic belt east of 104°E, in agreement with a flat Moho measured recently with a small linear array (Ye et al, 2017). We also note that the crust beneath the Liupan Shan at 36°N is~50-km thick, which is slightly thinner than the estimate of 55-60 km obtained from joint inversion of receiver functions and Rayleigh wave dispersions (Guo & Chen, 2017).…”
Section: Moho Topography and Crustal Poisson's Ratio From Receiver Fusupporting
confidence: 92%
“…By combing extensive data sets from these three seismic arrays, we constrain the crustal thickness and Poisson's ratio of our study region using receiver functions, and construct a 3-D S wave velocity (Vs) structure of the crustal and uppermost mantle by jointly inverting receiver functions and Rayleigh wave dispersions. Our study has much larger and denser station coverage than some previous studies that used the same method (e.g., Deng et al, 2018;Liu et al, 2014;Ye et al, 2017) and can thus clearly resolve the variations in crust and uppermost mantle structures across the entire eastern Tibetan plateau and surrounding regions in great detail.…”
Section: Introductionmentioning
confidence: 93%
“…The joint inversion method uses only the crustal part of P velocity model beneath the station, which is fixed as an input constraint. Ye et al () tested the influence of the uncertainty of the input Vp model (within 0.1 km/s) on the resulting models of the joint inversion and demonstrated that the main pattern of the final Vs and Vp/Vs models of the joint inversion is not affected. This is also clear when we tested joint inversions with different average Vp/Vs values assumed for the crust (Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al () applied the method to a profile in SE TP, where the Vp model was extracted from a 3‐D regional tomographic model. Ye et al () applied it to a dense profile across the eastern margin of the TP, where the Vp model was independently derived from an active refraction survey along the same profile.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation